Climate Change, Community Action, and Health in the Anglophone Caribbean: A Scoping Review - Sonja Lynn Myhre; Michelle Scobie; Eija Meriläinen; Eija Meriläinen; Eija Meriläinen; Ilan Kelman; Ilan Kelman; Unni Gopinathan (Public Health Reviews, 2024)
Objective: This scoping review investigates the status of research focusing on the nexus of community action, climate change, and health and wellbeing in anglophone Caribbean Small Island Developing States (SIDS).Methods: This review was guided by Arksey and O’Malley framework and utilized the PRISMA-ScR checklist. We searched Medline/OVID, PsychInfo, VHL, Sociological Abstracts, Google Scholar, and Scopus to capture interdisciplinary studies published from 1946 to 2021.Results: The search yielded 3,828 records of which fourteen studies met the eligibility criteria. The analysis assessed study aim, geographic focus, community stakeholders, community action, climate perspective, health impact, as well as dimensions including resources/assets, education/information, organization and governance, innovation and flexibility, and efficacy and agency. Nearly all studies were case studies using mixed method approaches involving qualitative and quantitative data. Community groups organized around focal areas related to fishing, farming, food security, conservation, and the environment.Conclusion: Despite the bearing these areas have on public health, few studies explicitly examine direct links between health and climate change. Research dedicated to the nexus of community action, climate change, and health in the anglophone Caribbean warrants further study.